Analysis of Investment Interest in Islamic Banks and Influencing Factors (A Study on Entrepreneurs in Sungai Penuh City) - Novera, Cici Mailina; Mu'arrif, Zul Ihsan; Yudeseman, Yudeseman (MediaTrend, 2024)
This research focuses on analyzing the investment interest of entrepreneurs in Sungai Penuh City, taking into account independent variables such as culture, trust, and service quality. The sampling method employed was simple random sampling, and data were obtained from 101 respondents who filled out the questionnaire both online and offline. The results of this study indicate the rejection of all three research hypotheses. Culture does not have a significant influence on investment interest. Trust also does not significantly affect investment interest. Additionally, service quality does not have a significant impact on investment interest. Overall, these findings affirm that statistically, culture, trust, and service quality do not have a significant influence on the investment interest of entrepreneurs in Sungai Penuh City.